Pengaruh Motivasi Kerja, Lingkungan Kerja dan Kepemimpinan Terhadap Kinerja Karyawan - Feby Dwi Cahyani; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Work motivation, work environment and leadership are factors that affect employee performance. This study aims to analyze and test how work motivation and work environment affect employee performance as an interference variable. Quantitative method is the method used in this research using descriptive analysis. Then using purposive random sampling method to collect data is done. The Slovin formula is used to calculate how many samples are taken in this study using a sample with 110 employees. The research will use an outer model that uses discriminant validity, composite reliability, Cronbach's alpha and an inner model that calculates r-square, f-square and path coefficient. The results of this study indicate that motivation at work, work environment conditions, and leadership have a positive and significant impact on employee performance.